Constituição e educação: autonomia universitária e a presença do Estado nas instituições de ensino superior particulares - Costa, Ilton Garcia da (2010)
The present study focuses on analyzing the Constitution and Education concerning the independence of universities and the normative and directive presence of the central government in universities, especially the private ones. The acts of the central government may, by means of norms, limit the independence of private universities, a fact that has inspired and founded the present study. In order to establish such interference, normative instruments have been analyzed, starting with the Federal Constitution, followed by the Law of Directives and Bases in Education, and including other legislation, from the perspective of Higher Education institutions. As the study developed, first the Federal Constitution was examined with respect to Education and their inter-connections. Next, Education was analyzed as a necessary and fundamental asset to achieve social justice, enforce public policies to ensure the quality of Higher Education; then the Law of Directives and Bases was examined regarding Higher Education, particularly education provided by private institutions, then the study compares the number of private versus public Higher Education institutions and, finally, the study looks into the central government s directive action in Higher Education and how it interferes with the independence of universities. The independence of universities has been analyzed from the point of view of pedagogical pluralism, freedom of choice and the actions meant to improve quality and bring excellence to Higher Education. The study has identified the need for directive action on the part of the central government on private Higher Education institutions to ensure quality, although within some parameters contemplated in this paper, and has confirmed the inescapable need for the independence of universities, whether public or private